(untitled) (Annals of Medical Research, 2021)
Aim: We aimed to compare the efficacy of Bascom cleft lift (BCL) and crystallized phenol application in the treatment of sacrococcygeal pilonidal sinus (SPS).Materials and Methods: This study included 83 SPS patients who were divided into two groups for treatment with either BCL (Group 1: n=30) or crystallized phenol (Group 2: n=53). The two groups were compared in terms of patient characteristics, perioperative results, rates of surgical site infection, hematoma and wound dehiscence, times of returning to daily activities, complete healing time and overall patient satisfaction.Results: The median follow-up was 40.3 (38.7-44.7) months. The length of hospital stay was longer in the BCL group than in the crystallized phenol group (P0.001). The median return to work or school was also slower in the BCL group than in the phenol group at 10 (3.2-7.7) and 3 (2-8.7) days, respectively (P=0.002). The phenol group were able to sit pain-free on the toilet earlier than the BCL group in 0.5 (1.1-9.7) and 3 (1.8-10.3) days (P=0.029), and also started lifting weights earlier 14.5 (6-50.2) days vs. 30 (18.1-41.6) days (P=0.011). Moreover, the phenol group reported greater patient satisfaction (P=0.004). On the other hand, the BCL group was more successful than the phenol group in terms of recurrence (P=0.082).Conclusion: Our results suggest that crystallized phenol can achieve higher patient satisfaction, less hospitalization time, and an earlier return to daily activities, school or work. On the other hand, Bascom cleft lift method results in less recurrence than crystallized phenol treatment.